THE DESIGN OF BANYUMAS REGIONAL PUBLIC HOSPITAL AT BANYUMAS DISTRICT - Louis
The Banyumas Hospital Mental Health Service Installation (Yankeswa) was appointed by the Ministry of Health and the Banyumas Regional Government as a national pilot project for mental health services at General Hospitals. But in reality, the installation conditions are still less than ideal. So it needs to be designed to comply with applicable standards. This final project aims to design a hospital building with layout modifications, increasing the number of floors, adding basement floors, and modifying room functions. The soil condition at the project review site has a site classification of SE, which is a type of soft soil and is quite vulnerable in the event of an earthquake. Based on the seismic design category in SNI 1726:2019, it was found that the structure of the review building is included in the seismic design category D (KDS D), so the building structure must be designed using a Special Moment Resisting Frame System (SRPMK). Modification of the number of storeys in the structure makes the structure more vulnerable to drift due to lateral earthquake loads that can occur, so the building structure is designed using lateral retaining structural elements, namely shear walls, which are included in the Special Structural Wall System (SDSK). So that in the superstructure system, this building will use a dual system (SRPMK + SDSK). The design of the superstructure is analyzed with the help of software in the form of ETABS for structural modeling and spColumn for detailing vertical elements such as columns and shear walls. For detailed structural elements, calculations were carried out with the help of MS Excel. The results of the structural design of the Detail Engineering Design drawings, which will be used as a reference in the construction process, Then, the substructure will be designed with a foundation system and a retaining wall system. The designed foundation system consists of piles with a diameter of 60 centimeters and a tip depth of 27 meters. In the design of the foundation, analysis of the axial bearing capacity of single pile and group pile, analysis of the lateral bearing capacity of single pile with the help of LPILE software, analysis of the lateral bearing capacity of group pile with the help of GROUP software, analysis of settlement and difference in foundation settlement, and design of the sloof or tie beam The results of the pile configuration design consist of 11 types of pile groups with different lengths and widths of pile caps but with the same height of 90 cm. The designed retaining wall system is a diaphragm wall with a wall depth of 16 meters and a wall thickness of 60 centimeters to accommodate basement needs and meet stability and deformation requirements. It requires steel strut reinforcement with an IWF 400.400.13.21 profile. During the excavation, dewatering is designed through six points with a total discharge of 420 liters per minute. Finally, construction management design will be carried out, which includes work breakdown structure, determination of construction implementation methods, construction safety management system, quantification of work volume, preparation of the project schedule, project cost estimation, and the project S curve. The construction method used is the bottom-up construction method, where the diaphragm wall, which functions as a retaining wall, uses the selected floor slab reinforcement. The field of construction management design includes geotechnical and structural fields, while architectural and MEP are designed using conceptual methods. The construction implementation method is determined based on environmental and safety aspects in the field. The calculation of detailed project costs used unit price and resource enumeration methods. The budget plan is determined based on direct and indirect costs and applicable taxes. Project scheduling is done using Ms. Project so that the implementation duration and S curve can be determined. The final result of the project design is a project value of Rp. 191,782,190.00. The project is planned for a duration of 20 months, or 620 calendar days.